Biomolecular imaging of host-pathogen interaction by Raman micro-spectroscopy - NAEMAT, ABIDA (2017)
The ability of pathogens and their surrogate host cells to exchange molecules is at the core of all host-pathogen interaction processes. Small chemical molecule signals provide a rich vocabulary for cellular communication, and pathogens have evolved the capacity to modulate, mimic or hijack these signals in a defensive, exponentially increasing the scope and complexity of this chemical language between host cells and pathogens. The objective of this work is to use Raman microscopy (RMS) to analyze molecular changes during infection of human cells by intra- (Toxoplasma gondii) and extra-cellular (Acanthamoeba castellanii) protozoan parasites. The work is divided into two parts. Firstly, we studied host-pathogen biomolecular interaction by using RMS. Secondly, we employed stable isotopes substitution technique to induce spectral changes that are specific to the labelled molecules. In this approach mammalian cells are selectively grown in culture medium in which only certain molecules are substituted with stable-isotope counterparts, and the exchange of these molecules are monitored between individual mammalian cells and parasites in real-time. Our results show that Raman spectroscopy can be a great tool to understand the molecular processes that mediate the interaction between the pathogens and host cell by providing quantitative spatially- and temporally-resolved information regarding molecular trafficking and exchanges. A better understanding of these complex interactions will advance our understanding of microbial pathogenesis and potentially identify new therapeutic targets.